Pemanfaatan Mobile JKN Untuk Meningkatkan Efektifitas Pelayanan: Studi Kasus BPJS Kesehatan Wonogiri - Sari, Erika Novita; Muslikhah, RR. Siti; Maisaroh (Program Sarjana Terapan Universitas Islam Indonesia, 2024)
The Mobile JKN application is a government innovation in the health sector managed by BPJS Kesehatan in providing public services to participants. This Mobile JKN application is expected to reduce queues at each BPJS Kesehatan branch office by helping to serve all participant administrative activities. However, many people do not have the Mobile JKN application and still, many participants come to the office for services. This study aims to determine the use of the Mobile Health Insurance (JKN) application to increase the effectiveness of services at BPJS Kesehatan Wonogiri Regency. This study uses a qualitative descriptive approach and data collection techniques through observation, interviews, and documentation. This study took informants as many as one staff and nine BPJS Kesehatan Wonogiri Regency participants. The study results show that participants' understanding and awareness of the Mobile JKN application is still low. The use of the National Health Insurance Mobile (JKN) application at BPJS Kesehatan Wonogiri Regency has been running. Still, it has not been effective and efficient in terms of measures of effectiveness, namely, program understanding, target accuracy, timeliness, achievement of goals, and real changes. The obstacles participants face in using the application are system disruptions, full storage of participants' mobile phones, and networks, participants who do not understand the application, and incomplete login requirements. Keywords: Utilization, Mobile JKN Application, Service Effectiveness